Implementation Of The Waterfall Model In Online Laundry Service Ordering Information Systems - Diyah Ruri Irawati; Marti Riastuti; Kokoy Rokoyah (Journal of Information System, Informatics and Computing, 2022)
Laundry Service is a laundry business that is engaged in services, laundry also offers a variety of services such as dry cleaning only, and ironing or ironing clothes only. The process of managing data for laundry facilities can be seen from the results of the analysis carried out. It still cannot be maximized and has several obstacles, including the accumulation of archives, reports, slow flow of information, slow processing and summary of data retrieval in transaction reports. To overcome this problem, a design and development of data management applications and laundry services was made. Applications made with the Waterfall system developer model include the steps of analysis, design, implementation, and system testing. The design is done using Unified Modeling Language (UML) data modeling which consists of Activity diagrams, Use Case Diagrams, Sequence Diagrams and Class Diagrams.